Association of alprazolam with major cardiovascular events in patients with hypertension. Issue 3 (6th August 2019) - Yeh, Chao‐Bin; Tsai, Ming‐Che; Teng, Ying‐Hock; Ku, Min‐Sho; Huang, Jing‐Yang; Wang, Bo‐Yuan; Tai, Chia‐Ling; Kornelius, Edy; Ho, Sai‐Wai
Abstract: Rationale: Anxiety is a mediator for emotional reactivity and acute blood pressure elevations, which are associated with an increased risk of cardiovascular death. Alprazolam is a common medication for anxiolysis. We hypothesized that alprazolam usage can reduce the risk of major adverse cardiovascular events (MACEs) in patients with hypertension. Methods: A retrospective cohort study was performed using datasets from Taiwanese Health and Welfare Data. Patients with hypertension were divided into exposed (Alprazolam‐exposed) and control groups (non‐Alprazolam‐exposed) with 1:1 propensity score matching. The study endpoint was the occurrence of MACE. Adjusted hazard ratio (aHR) of MACE risk was estimated using the multiple Cox proportional hazard model. Age‐stratified analysis was performed to evaluate the interaction of age and alprazolam use with MACEs. Results: The study cohort consisted of 335 517 alprazolam‐exposed patients and 1:1 PSM controls. The mean age was 63.62 ± 12.71 years in the Alprazolam‐exposed population. Alprazolam exposure was significantly associated with reduced risk of MACEs (aHR = 0.965, 95% CI = 0.954‐0.977), including ischemic stroke (aHR = 0.958, 95% CI = 0.940‐0.976), hemorrhagic stroke (aHR = 0.856, 95% CI = 0.821‐0.892), myocardial infarction (aHR = 0.933, 95% CI = 0.900‐0.968), sudden cardiac death (aHR = 0.955, 95% CI = 0.916‐0.996), and all‐cause mortality (aHR = 0.921, 95% CI = 0.909‐0.932). In the age‐subgroup analysis, alprazolam showed the greatest risk reduction effect in hemorrhagic stroke for patients aged <65 years (aHR = 0.779, 95% CI = 0.727‐0.835). Conclusion: Alprazolam usage in patients with hypertension was associated with a slightly reduced risk of MACEs and all‐cause mortality, and up to 22% reduced risk of hemorrhagic stroke was observed in alprazolam users aged <65 years.